Morphology and Composition of Inclusions in Si–Mn Deoxidized Steel at the Solid-Liquid Equilibrium Temperature - Gamutan, Jonah; Miki, Takahiro; Nagasaka, Tetsuya (Nippon Tekko Kyokai/Iron and Steel Institute of Japan, 2020)
Morphology and composition of inclusions change with temperature. However, besides the temperature conditions during steelmaking or continuous casting, other factors contributing to changes in the morphology and composition of inclusions during solidification are still unknown. In this study, the formation of complex inclusions in Si–Mn deoxidized steel after isothermal holding at the solid-liquid equilibrium temperature (TS) was investigated.